MAHASISWA DAN POLITIK KAMPUS STUDI KASUS PARTISIPASI MAHASISWA FISIP DALAM PEMILIHAN RAYA UNIVERSITAS RIAU TAHUN 2015 - Susanti, Susi; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Political participation is the activity of a person or group of people to participate actively in political life is to choose the leader of the State, and, directly or indirectly, influence government policy. Therefore the aim of this study to determine the factors - factors that affect the low involvement (participation) University students on Election Kingdom Riau Riau University in 2015. The theory is considered relevant in this matter is the Theory of Participation and Organization Theory. This research is a kind of quantitative methods of research, then for descriptive analysis of the data presented in the form of numbers by SPSS. The research conducted at the University of Riau and take samples of the data in the Faculty of Social and Political Sciences. This study uses the techniques of sampling of the population is involved directly or indirectly in the Electoral Kingdom University of Riau in 2015.PEMIRA University of Riau (UR) was first performed in 2002 in accordance with the results of the Riau University Student Congress IX in 2002 (one of the recommendations of Congress as well as change of Riau Puok Section IV, Article 2 of the President and Vice President of the Student directly). Later in 2015 The results of this study indicate the factors causing low levels of student participation which, seen from the socialization, the team's performance a success, popularity aspiring actor, and the involvement of students in the institution, but the results of the elections highway in 2015 when it carried out the socialization at the University of Riau particular Faculty of Social and Political Sciences students tend to participate less in terms of process pemlihan highway University of Riau, supposedly with this participation activities performed by students of Faculty of Social and Political Sciences can be more enthusiastic in terms of the electoral process highways University of Riau in 2015.Keywords: Participation, Election Kingdom, University of Riau